THE EFFECTIVENESS OF TAX COLLECTION WITH A DISTRESS WARRANT AT PRATAMA TAX OFFICE (KPP) OF NORTH MAKASSAR - Sari Sakinah; Syamsu Alam; Nur Wahyuni (Universitas Islam Balitar, 2019)
The purpose of this study is to determine the effectiveness level of tax collection by distress warrant at Pratama Tax Office (KPP) of North Makassar in the context of increasing tax revenues; to find out how much the contribution of tax collection with a distress warrant for the disbursement of tax arrears at Pratama Tax Office (KPP) of North Makassar. The study uses qualitative and quantitative data. It uses 2 data sources, library research and field research, the methods of data collection through interviews and direct observation. The method of analysis used in this research is comparative descriptive analysis, by describing, observing, collecting research data obtained from the object of research, and describing systematically, factually and accurately about the research then analyzed using the ratio technique. The results of this study indicate that the disbursement of tax arrears by distress warrant has not been fully achieved because sometimes taxpayers file objections or installments of payment of the tax debt. The contribution of active tax collection by distress warrant in 2016-2018 is classified as very poor in terms of tax revenue. The maximum level of effectiveness with distress warrant existed in 2017. Tax collection by distress warrant has increased from 2016 to 2018 both in terms of the number of sheets of distress warrant and the value of tax arrears written in distress warrant. Likewise, the disbursement of tax arrears with distress warrant has also increased both in terms of the number of tax arrears disbursement by distress warrant and the value of the disbursement of tax arrears in distress warrant.